Optimized nitrogen application increases rice yield by improving the quality of tillers. (3rd July 2022) - Zhou, Wei; Yan, Fengjun; Chen, Yong; Ren, Wanjun
ABSTRACT: The quantity and quality of tillers determine the yield of rice. In order to explore how optimized nitrogen fertilizer application (OFA) increases rice yield by affecting tiller growth, a pot experiment with three nitrogen treatments was performed on the basis of previous researches to investigate the growth and development of tillers. Results showed that under OFA, the emerging rate of secondary tillers and high leaf position tillers decreased, which increased with the number of primary tillers. The decrease of ineffective tillers increased the accumulation of biomass and nitrogen per tiller, which promoted the development of panicles. Compared with traditional nitrogen fertilizer application (TFA), the differentiated number of spikelets increased by 10.85%–21.70%, which led to the total number of filled spikelets increasing by 9.67%–18.95%, resulting in 9.6% increase in rice yield. Primary tillers, especially at the first, second, fifth, and sixth leaf positions, were the superior tillers in good quality, which made great contribution to rice yield and were significantly affected by nitrogen application. Making full use of the regulation effect of nitrogen on the quality of tillers will help to stabilize rice yield with less nitrogen input or increase rice yield without adding nitrogen input. Graphical abstract: uf0001